Superfícies associadas pela transformação de Ribaucour - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
In this paper we will study about Ribaucour Transformations and we will use the definition proposed by K.Tenenblat in [1]. We will study concerning the geometric aspects of such transformations and we will obtain as applications some Dupin surfaces in the R3 that are associated by a such Transformation. We will also present the visualization of those surfaces using resources of graphic computation.
Keywords: Superfícies de Dupin; Formas Diferenciais; Transformações de Ribaucour; Dupin Surfaces; Differential Forms; Ribaucour Transform; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA